Functional assertiveness with acceptance and commitment therapy for employees returning to work: a preliminary investigation - Daisuke Ito; Daisuke Ito; Yushun Okabe; Yushun Okabe; Aya Nobushige; Seiko Saito; Yoshinari Takahashi (Frontiers in Psychology)
Owing to the ongoing global mental health crisis, providing support for employees returning to work after a mental health leave has become a crucial issue. This study aimed to preliminarily examine the efficacy of a functional assertiveness training program incorporating acceptance and commitment therapy (ACT) in a pilot study involving individuals who had taken a leave of absence due to mental health problems. As part of the program, eight group sessions were offered to these individuals in a group format while they attended an outpatient psychiatric clinic. The effectiveness of the program was assessed in terms of mindfulness, psychological flexibility, functional assertiveness, and difficulty in returning to work. A total of 29 participants took part in the program, and 28 participants completed it. A paired t-test and effect size analysis (Cohen’s d) were conducted using data from 26 participants; two participants were excluded from the analysis due to post-test data was not collected. The results showed an increase in participants’ mindfulness (observing, non-reactivity and non-judging), psychological flexibility, and functional assertiveness increased and their sense of difficulty in returning to work (especially difficulties arising from workplace relationships) decreased after the intervention. Although the lack of a control group makes it difficult to draw definitive conclusions, the results suggest that a functional assertiveness training program incorporating ACT may be beneficial for employees on leave due to mental health issues in returning to work.